Hemovigilance Questionnaire in Pediatric Emergency and Pediatric Intensive Care Units - Alper Köker; Nazan Ülgen Tekerek; Perihan Aydın; Gökçe Aktuna; Oğuz Dursun (Galenos Yayinevi, 2022)
Introduction:Hemovigilance is a monitoring procedure that covers all transfusion steps from the collection of blood and blood components to the follow-up of end recipients. This procedure provides information about unexpected and undesirable effects caused by the use of blood products and evaluates them, and aims to prevent their occurrence and recurrence.Methods:Data were collected by filling in the questionnaire form created to determine the level of knowledge of pediatric emergency and pediatric intensive care nurses on blood and blood products transfusion via the online access link.Results:A total of 45 people answered the questionnaire sent. It was learned that 88.9% of the participants in the study completed undergraduate and graduate degrees. Of the responding nurses, 31 (68.9%) reported that there were hemovigilance nurses in their hospitals, and 39 (86.7%) received in-service training on the use of blood and blood products. The questions that the nurses gave the most wrong answers were about the storage periods of blood products. The question "If it is not transfused how long can the blood product be stored in the refrigerator for the longest time?" was answered correctly at a rate of 40%. The correct answer was 33.3% to the question "How long is fresh frozen plasma stored after thawing" and 20% to the question "What are the storage conditions of thrombocyte suspension". All the nurses answered, "If there is a reaction during transfusion, I will stop the transfusion".Conclusion:The hemovigilance system has emerged as a tool to increase the quality and safety of transfusions. This study provides data on the knowledge gaps of nurses who care for critically ill children. We think that the educations will contribute to hemovigilance practices by increasing the knowledge level of transfusion with both national-level pieces of training and in-service training for healthcare personnel.